2021
DOI: 10.3389/fimmu.2021.761326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DNA Methylation-Driven Genes-Based Prognostic Model and Drug Targets in Breast Cancer: In silico Screening of Therapeutic Compounds and in vitro Characterization

Abstract: DNA methylation is a vital epigenetic change that regulates gene transcription and helps to keep the genome stable. The deregulation hallmark of human cancer is often defined by aberrant DNA methylation which is critical for tumor formation and controls the expression of several tumor-associated genes. In various cancers, methylation changes such as tumor suppressor gene hypermethylation and oncogene hypomethylation are critical in tumor occurrences, especially in breast cancer. Detecting DNA methylation-drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It was previously thought to be an evolutionarily-related regulator of mitosis [ 34 ]. Recently, in the context of tumors, it has been shown to be associated with DNA methylation [ 35 ] and synergistic with P53 to promote tumor progression [ 36 ], but the correlation of lactic acid metabolism and immunotherapy has rarely been mentioned; Polo-like kinase 1 (Plk1) plays a key role in mitosis, which regulates cell proliferation. Studies on its transformation were mainly based on its phosphorylation and protein interaction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously thought to be an evolutionarily-related regulator of mitosis [ 34 ]. Recently, in the context of tumors, it has been shown to be associated with DNA methylation [ 35 ] and synergistic with P53 to promote tumor progression [ 36 ], but the correlation of lactic acid metabolism and immunotherapy has rarely been mentioned; Polo-like kinase 1 (Plk1) plays a key role in mitosis, which regulates cell proliferation. Studies on its transformation were mainly based on its phosphorylation and protein interaction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, therapy response of patients with ‘low miR-142-3p’ to dimethyl fumarate (DMF), an established disease-modifying treatment (DMT), was superior to that of patients with ‘high miR-142-3p’ levels ( 37 ). In addition, study had shown that by screening and analyzing data from the CTRP and PRISM databases, the potential target gene CDC25C has been identified as being linked to the drugs oligomycin A and panobinostat, providing potential therapeutic options for treating patients with high-risk breast cancer ( 38 ). Our in vitro studies on the function of CDC25C in NSCLC cells showed that CDC25C downregulation efficiently inhibited NSCLC cell invasion, migration, and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates the clinical applications of compounds from the CTRP and PRISM databases provide effective strategies and circumstantial evidence for the screening of drugs targeting KRAS mutations. These databases offer opportunities for drug repurposing, identification of combination therapies, personalized medicine approaches, and biomarker discovery ( 58 ). As for other genes whose expression in cell lines was inconsistent with the model, we hope that further verification can be carried out by other means, such as organoid models, in which the sensitivity of candidate drugs can be further verified.…”
Section: Discussionmentioning
confidence: 99%